Hukum Ayah Biologis Menikahi Anak Luar Nikah Menurut Madzahib Arba’ah dan KHI - Hamdan Hamdan; Suyud Arief; Ahmad Sobari (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
Examines the views of the fuqaha of four madhhab imams and the Compilation of Islamic Law (KHI) regarding children born out of wedlock. More detail is the problem of biological fathers marrying children born out of wedlock. This study aims to analyze the views of four madhhab imams and the Compilation of Islamic Law (KHI) on the marriage of biological fathers with children out of wedlock. This research is a research that uses quantitative descriptive method. namely describing the views of four imams of different schools of thought. Hanafi and Hanabilah scholars are of the opinion that it is haram. they argue that adultery can lead to haraam such as the prohibition of besanan (mushaharah) so that the marriage of a biological father with his child is unlawful. Meanwhile, according to the Malikiyah scholars, it is halal. and according to the Syafi'iyah scholars it is lawful but makruh. They argue that adultery cannot cause haraam such as the prohibition of besanan (mushaharah) so that the marriage of a biological father with his child is lawful. The Compilation of Islamic Law (KHI) argues that it is halal to marry a child born out of wedlock if it triggers the market 39 and article 100 of the Compilation of Islamic Law (KHI).